Generation And Aggregation Of Radiation Defects In Lif Crystals Under Gamma Irradiation - Mussaeva Malika Anvarovna; Nurimbetov Kurbanbay Keunimjay Ogli (Genius Journals, 2025)
The absorption spectra of LiF crystals irradiated with gamma radiation in a 60Co source at a power of 1200 R/s in the dose range of 105–108 R and a temperature of 320 K were studied. Gamma irradiation initially produces F -centers in the crystal, with an absorption band peaking at 250 nm and increasing in intensity with increasing dose across the entire range of doses studied. Increasing the irradiation dose leads to interactions between F - centers and the formation of more complex complexes, such as F2 - and F2⁺ - centers. The increase in the intensity of these bands, especially those of the R - and N- centers, at doses above 107 R indicates defect aggregation and the formation of stable color centers, which are the basis for the formation of nanoparticles in the crystal structure
Keywords: LiF crystal; optical absorption; color centers